PRODUCING STRAWBERRY (Fragaria chiloensis) DEHYDRATED Spray and lyophilization - Guevara Pérez, A. (1998)
Two methods of dehydration of strawberries (Fragaria chiloensis 1 .) ha ve been studied: spray-drying and freezedrying. It has been found that the optimum sequence for the drying operation is as follows: selection/classification , washing, steaming, pulp-extraction, conditioning and freeze-drying. The efficiency over the total solids obtained with this method is 86.48% compared to 66.02% when using spray-drying. The strawberry pulp was conditioned by water dilution of 1:1. For spray-drying, the pH was adjusted to 4.1 with NaHC03 , and for capsulating purposes were used: 1% CMC and 1.60% gum arabic by weight of pul p. For the dehydration by freeze-drying it was used: 1.2% CMC, 2.0% dextrine anda control sample without any additives. lt was found that for dehydration by spray-drying, 1.60% of gum arabic anda temperature of 1 802C for the hot air at the inlet should be u sed. For dehydration by freeze-drying, the strawberry sample without any additive turned out to have the best results in externa! appearance and taste, as well as a better retention of vitamine C (68.10%) compared with the results obtained by spray-drying treatment.